ADULT FEAR AND CONTROL: AMBIVALENCE AND DUALITY IN CLIVE BARKER’S THE THIEF OF ALWAYS (Imaginations: Journal of Cross-Cultural Image Studies, 2013)
This article considers the relationship between the text and accompanying illustrations in Clive Barker’s children’s novel The Thief of Always: A Fable. This tale of abduction was published in the social background of fear around the child predator of the early 1990s and incorporates ideas of monstrous villainy, loss of childhood innocence, and insatiable desires.  As a fable, Thief is a cautionary tale that not only teaches that childhood years are precious and are not to be wished away or squandered in idle leisure, but also of the dangers that some adults pose to children. Problematically, an honest and frank discussion of adult sexual desires toward children would despoil the very innocence that is trying to be protected; thus, a lesson such as this must be sublimated within the story. Yet, it is the illustrations, and more specifically the way in which the illustrations corroborate and contradict the plot of this story that reveals an underlying ambivalence toward the figure of the child and an echoing duality present in both the child and the child predator.